2014
DOI: 10.1111/are.12471
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of copepod nutritional quality as live food for aquaculture: a review

Abstract: In hatchery, an adequate supply of live food for first-feeding fish larvae is essential and nutritional quality of live food organisms can be improved through nutrient enrichment. The use of live food organisms, especially at first feeding, is a requisite for most marine fish larvae. In ocean, marine fish larvae primarily feed on copepods, but the production protocols of copepods as live food is underdeveloped in hatchery. As the food ingestion and the digestive system of copepods are different from other live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 197 publications
(280 reference statements)
2
64
0
Order By: Relevance
“…This is obtained when the R. salina algae are cultured at saturated irradiances and in nutrient excess condition. Previous studies showed that the increase in PUFA (including SC-PUFA and HUFA) in the algae diet would enhance the egg production and somatic growth of copepods (Rasdi and Qin 2014). Therefore, the relatively higher abundance of PUFA of R. salina cultured in saturated irradiances and in nutrient excess will benefit the performance of copepods.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is obtained when the R. salina algae are cultured at saturated irradiances and in nutrient excess condition. Previous studies showed that the increase in PUFA (including SC-PUFA and HUFA) in the algae diet would enhance the egg production and somatic growth of copepods (Rasdi and Qin 2014). Therefore, the relatively higher abundance of PUFA of R. salina cultured in saturated irradiances and in nutrient excess will benefit the performance of copepods.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the higher the level of relative abundance of PUFA content (including SC-PUFA and HUFA) in R. salina, the better it can be applied as feed for copepods (reviewed in Rasdi and Qin 2014). This is obtained when the R. salina algae are cultured at saturated irradiances and in nutrient excess condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations